2018
DOI: 10.3389/fpsyt.2018.00181
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Depression Treatment Including Internet-Based Interventions: Results From a Large Sample of Primary Care Patients

Abstract: Background: To date, little is known about treatment preferences for depression concerning new media. This study aims to (1) investigate treatment preferences for depression including internet-based interventions and (2) examine subgroup differences concerning age, gender and severity of depression as well as patient-related factors associated with treatment preferences.Methods: Data were derived from the baseline assessment of the @ktiv-trial. Depression treatment preferences were assessed from n = 641 primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 78 publications
5
27
1
1
Order By: Relevance
“…Interestingly, the present study contrasts the results of Dorow et al (18) who found that preferences for Internet-based interventions as part of depression treatment tended to decrease with age. Moreover, in a qualitative study aiming to investigate the acceptability of online self-management for depression in individuals with obesity, Löbner et al (43) found that also healthcare professionals consider younger patients as the preferred target group for iCBT use.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, the present study contrasts the results of Dorow et al (18) who found that preferences for Internet-based interventions as part of depression treatment tended to decrease with age. Moreover, in a qualitative study aiming to investigate the acceptability of online self-management for depression in individuals with obesity, Löbner et al (43) found that also healthcare professionals consider younger patients as the preferred target group for iCBT use.…”
Section: Discussioncontrasting
confidence: 99%
“…However, utilizing internet interventions for the treatment of mental disorders can also pose some challenges, such as low treatment commitment, incompatibleness of personal characteristics and treatment modality self-help, and missing or limited individualization options which may lead to higher dropout rates and decreased overall efficacy ( 29 31 ). To overcome some of these issues, their impact must be carefully considered during the study design phase and strategies to diminish negative effects should be incorporated, e.g., adherence monitoring, therapeutic contact through guidance, and individual tailoring.…”
Section: Introductionmentioning
confidence: 99%
“…This includes our work that shows that many patients with elevated depression are not identified as depressed by their doctors 7. Research by others has shown that patients have varied preferences for the management of psychological concerns 29. As a consequence, unlike other screening trials, our screening assessment covers both patient depressive symptoms and preferences for management.…”
Section: Research Ethics and Disseminationmentioning
confidence: 99%